Environmentally stable MXene ink for direct writing flexible electronics. Issue 17 (14th April 2022) - Kong, Na; Zhang, Jizhen; Hegh, Dylan; Usman, Ken Aldren S.; Qin, Si; Lynch, Peter A.; Yang, Wenrong; Razal, Joselito M.
Abstract : A long shelf time MXene ink was prepared using a mixture of water and ethylene glycol and is a promising candidate for fabricating conductive circuits and paper-based flexible devices. Abstract : MXene inks are promising candidates for fabricating conductive circuits and flexible devices. Here, MXene inks prepared from solvent mixtures demonstrate long-term stability and can be employed in commercial rollerball pens to write electronic circuits on flexible substrates. Such circuits exhibit a fast and accurate capacitive response for touch-boards and water level measurement, indicating the excellent potential of these MXene inks in electrical device fabrication.